2021
DOI: 10.3329/brc.v7i1.54247
|View full text |Cite
|
Sign up to set email alerts
|

Carbetocin versus Oxytocin in Active Management of 3rd stage of Labour following Vaginal Delivery

Abstract: Background: Every day more than 220 women around the world die from severe bleeding after childbirth. Globally post-partum hemorrhage is the number one direct cause of maternal mortality. Most postpartum hemorrhages are caused by uterine atony and occur in the immediate postpartum period. Most of these tragic deaths can be prevented by active management of third stage of labour. Active management of the third stage of labor should be practiced routinely to decrease the risk of postpartum hemorrhage. Oxytocin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…12 Ashraf et al documented mean ages of 23.9±3.2 years for the carbetocin group and 23.3±3.2 years for the oxytocin group, providing additional perspectives on the age distribution in these interventions. 13 In the current study, the mean age within group A was 24.9±3.7 years, while in group B, it was 24.5±3.8 years. Notably, Reyes and Gonzalez et al found that participants in the carbetocin group had a mean age of 26.5 years, while those in the oxytocin group had a mean age of 26.7 years.…”
Section: Discussionmentioning
confidence: 40%
See 4 more Smart Citations
“…12 Ashraf et al documented mean ages of 23.9±3.2 years for the carbetocin group and 23.3±3.2 years for the oxytocin group, providing additional perspectives on the age distribution in these interventions. 13 In the current study, the mean age within group A was 24.9±3.7 years, while in group B, it was 24.5±3.8 years. Notably, Reyes and Gonzalez et al found that participants in the carbetocin group had a mean age of 26.5 years, while those in the oxytocin group had a mean age of 26.7 years.…”
Section: Discussionmentioning
confidence: 40%
“…In contrast, the oxytocin group exhibited higher rates, with 15.5% and 10.6% requiring blood transfusion in separate studies. 13,14 In the current study, none of the patients in group A necessitated fundal massage, while in group B, 9% of patients required it. This trend is consistent with the findings of Ashraf et al 13 Moreover, Agnes et al observed that 10% of patients in the carbetocin group and 83% in the oxytocin group required fundal massage, highlighting a notable difference in the demand for this intervention between the two drug groups.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations